Redefinition of the Indonesia Land Agency's GNSS CORS Coordinate for Cadastral Survey Control Points - Putraningtias, M. Elya Lim; Heliani, Leni Sophia; Widjajanti, Nurrohmat (2018)
Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (Kementerian Agraria dan Tata Ruang (ATR)/Badan Pertanahan Nasional (BPN) utilizes GNSS CORS technology known as JRSP to perform cadastral measurement and mapping. The definition of the GNSS CORS base station coordinates is carried out following the reference system at the time of construction. To produce cadastral measurements with accurate and precision meet the cadastral mapping specifications, it is required reference frame with accurate coordinate. Therefore, the redefinition coordinate of base stations is performed by BPN periodically. These are delivered to monitor and update base station positions to accommodate Indonesian geodynamics and to ajust the specifications. Also, the quality of receivers at the base stations also need to be monitored. The zero baseline tests are used to check the GNSS receiver accuracy. The results of the redefinition and calibration of GNSS CORS receiver show the effect of base station stability, movement of earth dynamics, migration of base station location, and change of receiver antenna quality.